A formação e o desenvolvimento do leitor literário: a narrativa arquetípica do herói e a mitologia na sala de aula - ARAÚJO, Roberto Pinheiro (Universidade Federal do Pará, 2017)
The dissertation "The formation and development of the critical reader: the archetypal narrative of the hero and the mythology in the classroom" Corresponded to a study of the role of literature in school, having as support the archetypal narrative of the hero and the comparative study of the myths in its proposal of intervention. We aimed to provide a reflection on what has been done in the school environment in relation to Literature and what it is necessary to do for the constitution of the reader subject and thus contribute to the debate about the role of reading Literature in school. In order to do so, we have adopted the work done by Solé (1998), Antunes (2014), Menegassi (2005/2010) and Lopes-Rossi (2008) regarding the linguistic theory and Cosson (2014) literary text reading. As for the study of myths, we used Campbell (2002, 2003), Eliade (2011/2002), Salis (2003) and Kenneth (2015). Finally, in order to base and support the construction of our conception of study that takes into account the language in the process of interaction, Bakhtin/Voloshinov (1999) works on the dialogical character of language. We had as target audience the students of the 8th year of Elementary School of the State Public Network, Characterized as novice readers, with some reading processing skills not yet satisfactorily developed. The pedagogical activities that constituted the intervention proposal presented strategies that aimed to broaden the world view of these students, from the recognition of patterns and the dialogue between mythological texts of different cultures and their presence in our daily life among other genres. This proposal, it is considered the extrapolation of the text and the exploration suggested thematic by a literary work enables the student to recognize other dimensions of the narrative, arousing political, philosophical, moral reflection. We adopted, in the methodological aspect the qualitative research of an applied nature, trying to observe the daily school life, the harsh reality faced by educators and students, from the obtained reports and stories, we created and applied our proposal of intervention. At the end of this work, we selected some productions of the students to weave analyzes, verify and debate about the results of the application of the activities in the school, in their positive and negative aspects.